2008
DOI: 10.1089/jwh.2007.0621
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Smoking Behaviors in an Asian Population

Abstract: Background: Gender-sensitive tobacco control policies are being challenged, and new directions are being sought because public health efforts have reduced cigarette consumption more substantially among men than among women. To better target women, it would help to identify the protective cultural factors that promote resiliency in women and discourage them from smoking. Whereas western cultures have generated a great deal of gender-specific research and programs on the prevention of smoking in women, Asian cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
86
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(97 citation statements)
references
References 22 publications
6
86
0
2
Order By: Relevance
“…Differences in the smoking behavior of men and women were reported in a 2004 cross-sectional survey in Taiwan, with the smoking rate ratio of males/females being 9.5 (45.7% vs 4.8%) and the observation that men smoked significantly more cigarettes per day (18 vs 11). 22 Smoking is an important risk factor for lung cancer that could account for the sex discrepancy of the lung cancer incidence in our study.…”
Section: Discussionmentioning
confidence: 58%
“…Differences in the smoking behavior of men and women were reported in a 2004 cross-sectional survey in Taiwan, with the smoking rate ratio of males/females being 9.5 (45.7% vs 4.8%) and the observation that men smoked significantly more cigarettes per day (18 vs 11). 22 Smoking is an important risk factor for lung cancer that could account for the sex discrepancy of the lung cancer incidence in our study.…”
Section: Discussionmentioning
confidence: 58%
“…In contrast, previous reports by other investigators have indicated that the RR for lung cancer mortality in US White smokers ranges from 8.1-22.4 that is much greater than those found in Asians, ranging from 2.7 to 3.8 [18]. As less than 5% of the female population in Taiwan smoke [2,3], the PM 2.5 breathed by Asian females seems to be responsible for a larger proportion of lung cancer deaths than those that could possibly be predicted by the first and second hand smoking. One reason could be due to the difference in the exposure concentrations (mean: 35.6 in Taiwan vs less than 20 µg/m 3 in the US) and/or the difference in the component composition of PM 2.5 .…”
Section: Discussionmentioning
confidence: 65%
“…Both ACS [25] and Harvard sixcities studies [26] on PM 2.5 followed this non-threshold assumption. The 20 µg/m 3 floor set up in our study may seem like a threshold, but this was done out of the reality that the lowest mean concentration throughout Taiwan was around 20 µg/m 3 and not much less in each of the 290 townships. The floor of 20 µg/m 3 reflects the high PM 2.5 exposure in Taiwan and the necessity to have a reference exposure group for calculating relative risks.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Whereas men smoke in response to social stimuli related to their environment and social structure, women are more likely to smoke to relieve stress and induce weight loss. (Tsai et al, 2008), (Fidler and West, 2009) Although enjoyment and stress relief are well-known motivations for smoking, many people also believe that smoking helps to control weight, (Grunberg, 1997) leading to many studies on the relationship between smoking and weight loss. (Mack et al, 2004;Spring et al, 2009) A recent study showed that current smokers were greatly concerned with their weight and former smokers were on a diet to prevent cessation-related weight gain.…”
Section: Introductionmentioning
confidence: 99%